Forecasting in constructing scenarios for assessing profitability and risk of investing in real property - Krupowicz, Joanna (Prognozowanie w konstrukcji scenariuszy do oceny opłacalności i ryzyka inwestowania w nieruchomości, 2011)
The paper presents scenario analysis – one of the methods of calculating effectiveness of investing in real property. It is suggested to use forecast methods in constructing scenarios. In addition, the issue of the number of generated scenarios is presented and the creation thereof is suggested based on scenarios for individual explanatory variables.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 83-91
Keywords: inwestowanie; prognozowanie; nieruchomości; investing; forecasting; real estate